Katunga lapas sa kagahapon - Pagusara, Don (2015)
With 6 poems by Urias Almagro: "hikat-oni," "itom nga bino," "ang pabilo," "buot ko unta," "huni," and "umaagi"
Keywords: Almagro, Nyor Urias; Poems -- Cebuano language